Rate of anticoagulant use, and factors associated with not prescribing anticoagulant in older Thai adults with non-valvular atrial fibrillation: A multicenter registry - Rungroj Krittayaphong (2019)
©2019 JGC All rights reserved. Objectives To investigate the rate of anticoagulant use, the reasons for not prescribing anticoagulant, and the factors associated with non-prescription of anticoagulant in older Thai adults with non-valvular atrial fibrillation. Methods A multicenter registry of patients with non-valvular atrial fibrillation was conducted during 2014 to 2017 in Thailand. Demographic, medical history, antithrombotic medication, non-antithrombotic medication, and laboratory data were collected and analyzed. Data were compared between the older adult (≥ 65 years) and younger adult (< 65 years) groups. The reasons why anticoagulant was not prescribed were collected, and predictive factors were identified. Results A total of 3218 patients (1873 males) with an average age of 67.3 ± 11.3 years were included. Almost two-thirds (61.0%) of patients were in the older adult group. Anticoagulant was prescribed in 2422 patients (75.3%): 81.4% in the older adult group and 65.7% in the younger adult group. The three main reasons for not prescribing anticoagulant were already taking antiplatelets, patient refusal, and bleeding risk. These reasons were more common in older adults as compared to younger adults. Multivariate analysis revealed current use of antiplatelets to be the most important factor that predict the non-prescription of anticoagulant in older population. Conclusions The prevalence of anticoagulant prescription among older Thai adults with atrial fibrillation is 81.4%. Taking antiplatelet drugs was found to be the strongest reason that predicts the non-prescription of anticoagulant in this patient population. A guideline should be developed to optimize the use of anticoagulant and antiplatelet in older adults.